2015
DOI: 10.1177/1074248414568196
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Preconditioning Attenuates Myocardium Ischemia-Reperfusion Injury Through Upregulation of Heme Oxygenase 1 Expression

Abstract: These data present a novel signaling mechanism by which hyperbaric oxygen preconditioning protects myocardium ischemia-reperfusion injury via PI3K/Akt/Nrf2-dependent antioxidant defensive system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 54 publications
1
22
0
2
Order By: Relevance
“…20,41,42 In our study, we investigated the effects of Nar on the Nrf2 translocation and phosphorylation of AKT, PKCδ, and ERK1/2 at different time points. 20,41,42 In our study, we investigated the effects of Nar on the Nrf2 translocation and phosphorylation of AKT, PKCδ, and ERK1/2 at different time points.…”
Section: Discussionmentioning
confidence: 99%
“…20,41,42 In our study, we investigated the effects of Nar on the Nrf2 translocation and phosphorylation of AKT, PKCδ, and ERK1/2 at different time points. 20,41,42 In our study, we investigated the effects of Nar on the Nrf2 translocation and phosphorylation of AKT, PKCδ, and ERK1/2 at different time points.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HBO therapy may attenuate hypoxia in marginally perfused tissue (sometimes referred to as the "ischemic penumbra"), and this may be useful in avoiding cell death and restoring function [17]. Recent research suggests that HBO prevents myocardium from ischemia injury by suppression of apoptotic pathways (blockage of caspase-3 activity and protection against Bax/Bcl-2-mediated apoptosis) [18] and protects MIRI via PI3K/Akt/ Nrf2-dependent antioxidant defensive system in animal models [19]. Moreover, for people with acute coronary syndrome, there is some evidence from clinical trial to suggest that HBO is associated with a reduction in the risk of death, the volume of damaged muscle and the risk of major adverse cardiac events [20].…”
Section: Introductionmentioning
confidence: 99%
“…The lower levels of roS indicated by dHe oxidation may have resulted from increased Sod and caT expression. although the mechanisms by which HBo therapy induces an antioxidant response remain unclear, it has been reported to involve a nrf2-dependent effect (43,44) triggered in a pro-oxidizing environment (31). indeed, we observed that HBO decreased the GSH/GSSG ratio, confirming such nrf2-inducing conditions.…”
Section: Discussionmentioning
confidence: 99%